Molecular Analysis of Escherichia coli and Correlations Between Phylogroups and Sequence Types from Different Sources - João Gabriel Material Soncini; Vanessa Lumi Koga; Bruna Fuga; Zuleica Naomi Tano; Gerson Nakazato; Renata Katsuko Takayama Kobayashi; Nilton Lincopan; Eliana Carolina Vespero (Microorganisms)
Escherichia coli is a significant pathogen responsible for infections in both humans and livestock, possessing various virulence mechanisms and antimicrobial resistance that make it even more concerning. In this study, several internationally recognized clones of E. coli were identified, such as ST131, ST38, ST648, and ST354, from chicken meat, pork, and human infection samples. Notably, ST131, belonging to phylogroup B2, was the dominant sequence type (ST) in human samples, while ST38, belonging to phylogroup D, was the most prevalent in meat samples. Several antibiotic resistance genes were identified: the gyrA gene mutation was the most prevalent, and CTX-M-55 was the most common extended-spectrum beta-lactamases (ESBLs), with significant differences noted for CTX-M-2 and CTX-M-15. Virulence-associated genes (VAGs) such as gad and iss were frequently found, especially in human isolates. These findings highlight the complex epidemiology of antibiotic-resistant E. coli in community settings and the potential risks associated with commercial meat.